Incidence of intraepithelial fallopian tube neoplasias in mexican women over 40 years of age that underwent elective hysterectomy - Antonio Gabriel Briseño Campos; Antonio Cruz Rodríguez; Martha Olivia García Perales; Francisco Javier Serna Vela; Diana Gabriela Camarillo Elizalde; María del Consuelo Robles Martínez (Journal of Ovarian Research, 2019)
Abstract Aims The incidence of intraepithelial neoplasia in the fallopian tubes of women over 40 years of age who had undergone elective hysterectomy was assessed at the Aguascalientes Women’s Hospital. Methods An observational, prospective, descriptive study was carried out at the Aguascalientes Women’s Hospital on female patients over 40 years of age who underwent elective hysterectomy between July and October 2017. In these 4 months, 85 patients underwent elective hysterectomy. Results In this study, 85 patients who received a hysterectomy for non-oncological reasons were analyzed. Salpinx alterations compatible with intraepithelial neoplasia in the Fallopian tubes were found in 2.4% of the patients studied. Conclusions The incidence of intraepithelial neoplasia in the fallopian tubes of high-risk patients at the Aguascalientes Women’s Hospital is 2.4%. Prophylactic salpingectomy is a simple procedure and has the potential to decrease the risk of high-grade ovarian cancer. In premenopausal patients, total abdominal hysterectomy with bilateral salpingectomy should be the procedure most often performed.